A Novel RFID EMSICC-based Chipless Tag - Sakouhi, Soumaya; Raggad, Hedi; Gharsallah, Ali; Latrach, Mohamed (Společnost pro radioelektronické inženýrství, 2017)
A new Radio Frequency Identification (RFID) chipless tag based on the Substrate Integrated Waveguide (SIW) technology is proposed in this paper. The tag highlights the importance of using such technologies allowing a surface miniaturization, a high Q-factor and an original shape. Thus, the novel design consists of an Eight-Mode Substrate Integrated Circular Cavity (EMSICC) associated to an Ultra Wideband (UWB) bowtie-shaped antenna. The EMSICC is realized by bisecting the Quarter Mode Substrate Integrated Circular Cavity (QMSICC) into two parts, while preserving the same resonant frequency and the original electric field distribution. Further, the operating frequency band is from 5 GHz to 8 GHz within a compact area of 4.97 × 1.05 cm2. The proposed design is experimentally validated in the frequency domain.
Keywords: RFID; chipless tag; Substrate Integrated Waveguide (SIW); Substrate Integrated Circular Cavity (SICC); Half Mode SICC; Quarter Mode SICC; Eight-Mode Substrate Integrated Circular Cavity (EMSICC); EMS (Electromagnetic Signal)